2013
DOI: 10.3892/etm.2013.1073
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution and the relative risk factors for human papillomavirus in Urumqi, China

Abstract: The aim of this study was to investigate human papillomavirus (HPV) infection and HPV genotype distributions in Urumqi, Xinjiang, China. The related risk factors for high-risk HPV infection was also analyzed. A stratified cluster sampling method was used for the population-based cervical cancer screening of women aged 18–69 years in the Urumqi Saybagh district. Exfoliated cervical cell samples were collected for liquid-based cytology detection and HPV genotyping DNA microarrays. Education level, number of sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Additionally, the HPV infection conditions in China varied in different provinces and cities . However, HPV‐16, HPV‐58, and HPV‐52 were the top three most common types in most regions of China . The present study showed that the HPV infection rate among women in Shaanxi province was 30.21%, the HR‐HPV infection rate was 26.73%, and the five most common HR‐HPV types were HPV‐16, HPV‐58, HPV‐52, HPV‐31, and HPV‐18, indicating that HPV‐52 and HPV‐58 might have a higher prevalence rate in China than HPV‐18, which was more common in other countries in the world …”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the HPV infection conditions in China varied in different provinces and cities . However, HPV‐16, HPV‐58, and HPV‐52 were the top three most common types in most regions of China . The present study showed that the HPV infection rate among women in Shaanxi province was 30.21%, the HR‐HPV infection rate was 26.73%, and the five most common HR‐HPV types were HPV‐16, HPV‐58, HPV‐52, HPV‐31, and HPV‐18, indicating that HPV‐52 and HPV‐58 might have a higher prevalence rate in China than HPV‐18, which was more common in other countries in the world …”
Section: Discussionmentioning
confidence: 61%
“…The HR-HPV prevalence in the Han women was in line with the previously reported infection rate for Qujing City, Yunnan (8.3%), and the Autonomous Tibet (8.0%) prefecture [ 26 , 33 ]. However, the HR-HPV prevalence in the Hani women was higher compared with other ethnic minority groups in China, such as the Uyghur (7.3%) [ 34 ] and Maonan (7.6%) group, [ 35 ] but lower than Tibetan (26.2%) and Han (16.6%) groups in Northwestern Yunnan. However, the reported HR-HPV prevalence rates in Naxi group (11.4%) in Northwestern Yunnan [ 11 ], Zhejiang (10.2%), and Shanxi (12.2%) are in line with our observations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the development of tumor immunology and molecular biology, biological treatment has become the fourth treatment method for malignant tumors [ 2 ]. The incidence of cervical cancer in Xinjiang Uygur women is significantly higher than that in women of other ethnic groups, with an average age of onset at 43 years old [ 3 ]. In Xinjiang Autonomous Region, cervical cancer severely threatens the health and life quality of Uygur women and has become an important public health problem [ 4 ].…”
Section: Introductionmentioning
confidence: 99%